2007
DOI: 10.1002/cne.21262
|View full text |Cite
|
Sign up to set email alerts
|

Differential hypertrophy and atrophy among all types of cutaneous innervation in the glabrous skin of the monkey hand during aging and naturally occurring type 2 diabetes

Abstract: Diabetic neuropathy (DN) is a common severe complication of type 2 diabetes. The symptoms of chronic pain, tingling, and numbness are generally attributed to small fiber dysfunction. However, little is known about the pathology among innervation to distal extremities, where symptoms start earliest and are most severe, and where the innervation density is the highest and includes a wide variety of large fiber sensory endings. Our study assessed the immunochemistry, morphology, and density of the nonvascular inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 131 publications
(189 reference statements)
2
106
0
Order By: Relevance
“…It should also be noted that studies of human skin of patients with complex regional pain syndrome type 1 and postherpetic neuralgia and studies of rhesus monkeys with type 2 diabetes have revealed significant structural and chemical pathologies among the various components of the skin that normally express H 3 Rs in rats and mice. These include not only perivascular A␦ fibers, but also epidermal keratinocytes, A␤ fiber Meissner's corpuscle endings, and lanceolate endings (Petersen et al, 2002;Albrecht et al, 2006;Cannon et al, 2007a;Paré et al, 2007;Zhao et al, 2008).…”
Section: H 3 Rs In Models Of Chronic Painmentioning
confidence: 99%
“…It should also be noted that studies of human skin of patients with complex regional pain syndrome type 1 and postherpetic neuralgia and studies of rhesus monkeys with type 2 diabetes have revealed significant structural and chemical pathologies among the various components of the skin that normally express H 3 Rs in rats and mice. These include not only perivascular A␦ fibers, but also epidermal keratinocytes, A␤ fiber Meissner's corpuscle endings, and lanceolate endings (Petersen et al, 2002;Albrecht et al, 2006;Cannon et al, 2007a;Paré et al, 2007;Zhao et al, 2008).…”
Section: H 3 Rs In Models Of Chronic Painmentioning
confidence: 99%
“…These can be at multiple sites along the axons, including distal terminals. Evidence from earlier studies has implicated multiple sites in the generation of ectopic activity, including peripheral nerve terminals (Albrecht et al, 2006;Kauppila et al, 2002;Pare et al, 2007), at the site of nerve injury (Bird et al, 2007;Coward et al, 2000;Devor et al, 1993;Novakovic et al, 1998;Omana-Zapata et al, 1997a,b;Tal and Eliav, 1996), along the nerve (Amir et al, 2005;Gold et al, 2003;Pertin et al, 2005), adjacent nerves (Sotgiu et al, 2006), and in the dorsal root ganglia (Amir et al, 1999;Chaplan et al, 2003;Craner et al, 2002;Liu et al, 2000bLiu et al, , 2002Michaelis et al, 2000;Na et al, 2000;Novakovic et al, 1998;Omana-Zapata et al, 1997a,b;Study and Kral, 1996;Xie et al, 1995).…”
Section: Site Of Generation Of Peripheral Drivementioning
confidence: 99%
“…The literature describing cutaneous innervation in non-human primates with diabetes is currently limited to a single paper assessing innervation of glabrous skin from monkeys with naturally occurring type 2 diabetes (Pare et al, 2007). Biopsies from monkeys with short-term hyperglycemia showed a hypertrophy of epidermal nerve fibers.…”
Section: Animal Modelsmentioning
confidence: 99%